The Role of Organizational Innovation in Organizational Immunity: The Mediating Role of Participative Leadership - Yazin Salim Muhammed (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aimed to determine the mediating role of participatory leadership in organizationalimmunity by examining its application in Kerbala Cement Company. To accomplish this, the aspectsof organizational innovation (product innovation, process innovation, and administrative innovation)were chosen above organizational immunity in its dimensions (organizational learning, memory, andDNA). Participatory leadership strengthens this relationship in its dimensions (delegation of powers,participation in decision-making, participation in information, and human relations). A random sampleof employees in Kerbala Cement Company was selected as a field of research through a questionnairethat included (128) individuals. The significance of the correlation between the two variables wasassessed using the (t) test, the regression model's significance was assessed using the (F) test, and thesimple correlation coefficient (Person) was used. The relative quantity the independent variablecontributes to explaining the dependent variable as a percentage was also determined using (R 2 ). Theresearcher's most notable conclusion is that participatory leadership serves as a mediating factor in thesubstantial impact of organizational innovation on organizational immunity. The research concludedwith several recommendations, including focusing on organizational innovation by Kerbala CementCompany because it is an important factor in its work in general and in organizational immunity inparticular.